Maturity of knowledge management evaluation in organizational units using Data Envelopment Analysis - Nazila Adabavazeh; Mehrzad Navabakhsh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The global economy has shifted from being resource-based to knowledge-based. Leading organizations create more value-added and long-term competitive advantage by managing their intellectual assets more than ever. Knowledge management is one of the most common processes through which an organization generates wealth from its knowledge and intellectual capital. Knowledge management empowers innovation. On the other hand, today, knowledge is the only reliable source for creating sustainable competitive advantage in organizations. The present research evaluates organizational maturity using knowledge management through data envelopment analysis. Methodology: The present research is goal-oriented, applied, and developmental. The population consists of 6 organizational units of the studied company. The theoretical framework of the research is derived from the Tark Zade (0212) knowledge management maturity model. The input, total component of the knowledge management maturity model, and the maturity level indicator are calculated. Lingoes software was used for data analysis. An input-oriented data envelopment analysis model was used to determine the highest efficiency ratio and to intervene in the optimal weighting of inputs and outputs of other decision-making units for the unit under study. Findings: Based on the study results, it is expected that the level of organizational knowledge management maturity can be significantly enhanced by providing control measures. The most critical control solutions include training, organizational and individual learning, knowledge sharing, innovation, and formulating a knowledge vision and strategy to guide knowledge management initiatives. Originality/Value: Combining these two sets of knowledge management and organizational maturity helps organizations increase the effectiveness of their processes and identify critical issues.